DIGITAL LEGAL EDUCATION FOR LOW-INCOME POPULATIONS: STRATEGIES BASED ON SIMPLIFIED MULTIMEDIA CONTENT - dos Reis, Renato de Carvalho (Revista Sistemática, 2023)
Socioeconomic inequality significantly limits low-income populations’ ability to understand fundamental rights and institutional mechanisms for accessing justice. This article analyzes digital legal education strategies grounded in simplified multimedia content, based on a structured literature review of peer-reviewed studies published between 2020 and 2025. The review examined research addressing digital platforms, community web applications, audiovisual legal programs, gamified educational models, and digital communication strategies targeting vulnerable populations. Findings indicate that approaches aligned with the Cognitive Theory of Multimedia Learning, combined with accessible language and inclusive instructional design, enhance comprehension of complex legal information. Thematic segmentation, storytelling, reduced textual density, and interactive features are consistently associated with improved retention and engagement. However, methodological limitations remain, particularly regarding longitudinal measurement of real-world impact on access to justice. The study concludes that digital legal education can mitigate structural informational barriers when implemented through clearly defined technical, pedagogical, and sociocultural criteria grounded in evidence-based instructional design.